Stormwater, watershed, and receiving water quality modeling (Water Environment Federation, 2020)
Traces the history and evolution of stormwater quality modeling and provides a roadmap of the model selection process based on model capabilities and user needs. Includes a reference guide into state-of-the-art and state-of-practice stormwater models as well as side-by-side comparison of land-based and receiving water quality simulation models.